2020
DOI: 10.14746/ssllt.2020.10.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Task repetition and collaborative writing by EFL children: Beyond CAF measures

Abstract: Research into the potential of collaborative writing is relatively new. Similarly, task repetition (TR), which has been claimed to be a valuable tool for language learning, has been rarely explored in the context of writing. Therefore, little is known about the potential of combining TR and collaborative writing, and even less if we focus on young learners (YLs), who constitute a generally under-researched population. With these research gaps in mind, the present study examines the compositions of 10 pairs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 49 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…In recent years, external exact TR with and without feedback has come to the forefront of writing research thanks to its potential to improve written drafts and offer learning opportunities, in particular, with learners writing in collaboration, as students can deliberate, give feedback to each other and write better texts (Storch, 2013 for a summary). Thus, several empirical studies focusing on external TR without the provision of feedback have proved the potential of repeating the exact same writing task several times to improve the written products of adults (Amiryousefi, 2016;Kim, Kang, et al, 2020) and children (Hidalgo & Lázaro-Ibarrola, 2020;Lázaro-Ibarrola & Hidalgo, 2021), although the specific learning outcomes reported by different studies are far from homogeneous. For instance, regarding adult populations, Nitta and Baba (2014) conducted a unique piece of research on the effects of mass TR with forty-six first-year Japanese university students.…”
Section: Task Repetition and Motivation In The Context Of Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, external exact TR with and without feedback has come to the forefront of writing research thanks to its potential to improve written drafts and offer learning opportunities, in particular, with learners writing in collaboration, as students can deliberate, give feedback to each other and write better texts (Storch, 2013 for a summary). Thus, several empirical studies focusing on external TR without the provision of feedback have proved the potential of repeating the exact same writing task several times to improve the written products of adults (Amiryousefi, 2016;Kim, Kang, et al, 2020) and children (Hidalgo & Lázaro-Ibarrola, 2020;Lázaro-Ibarrola & Hidalgo, 2021), although the specific learning outcomes reported by different studies are far from homogeneous. For instance, regarding adult populations, Nitta and Baba (2014) conducted a unique piece of research on the effects of mass TR with forty-six first-year Japanese university students.…”
Section: Task Repetition and Motivation In The Context Of Writingmentioning
confidence: 99%
“…As for YLs, very few studies have focused on external exact TR without the provision of WCF so far. Hidalgo and Lázaro-Ibarrola (2020) examined the compositions of 10 pairs of primary school EFL learners (aged 12) who wrote the same text in response to the same picture prompt three times over a three-week period. The compositions improved with repetition when measured by holistic ratings (although not when measured by CAF measures).…”
Section: Task Repetition and Motivation In The Context Of Writingmentioning
confidence: 99%
“…It is in line with Bikowski & Vithanage (2016) who found that students in collaborative revision web-based writing experienced statistically significant writing improvement. Additionally, writing together may offer students occasions to use the target language in a meaningful context and share their knowledge on language use and combined with the repetition of the same draft, which enabled learners to produce a better final text (Hidalgo & Lázaro-Ibarrola, 2020). Through collaborative interaction, students feel freer to explore and discuss other relevant ideas that can enrich their writing tasks (Taalas et al, 2018) and collaborative writing gives some benefits to students during the learning process i.e., enhance their collaboration, communication, and problem-solving skills.…”
Section: Discussionmentioning
confidence: 99%
“…The students have further interaction in the class as it involves social relations between group members (Nykopp et al, 2019) and giving or getting some feedback for their writing revision, where collaborative revision allows students to produce more grammatically accurate text (Villarreal & Gil-Sarratea, 2020). Hidalgo & Lázaro-Ibarrola (2020) believe that collaborative writing combines the benefits of oral interaction and writing tasks. During the interaction, learners engage in meaningful use of the target language and have opportunities to negotiate for meaning and produce modified output.…”
Section: Discussionmentioning
confidence: 99%
“…As they are communicating for meaning, communicative breakdowns may occur and students may ask clarification questions, ask for repetition, and discuss specific lexical items, which boosts AL development (Kim, 2015). An added benefit is that students repeat their information (this time to students who have not read the same text), and through repeated output, research has shown benefits for EAL learners (Hidalgo & Lázaro-Ibarrola, 2020;Shintani, 2018). During the implementation of this task, there was no requirement to produce output about the two new organizations (no note-taking activity).…”
Section: Explanationmentioning
confidence: 99%